A Nitroxide‐Tagged Platinum(II) Complex Enables the Identification of a DNA G‐Quadruplex Binding Mode. Issue 10 (4th February 2016) - Xu, Cui‐Xia; Zhang, Xiaojun; Zhou, Yi‐Wei; Wang, Hanqiang; Cao, Qian; Shen, Yong; Ji, Liang‐Nian; Mao, Zong‐Wan; Qin, Peter Z.
Abstract: We reported a novel strategy for investigating small molecule binding to G‐quadruplexes (GQs). A newly synthesized dinuclear platinum(II) complex (Pt2 L) containing a nitroxide radical was shown to selectively bind a GQ‐forming sequence derived from human telomere (hTel). Using the nitroxide moiety as a spin label, electron paramagnetic resonance (EPR) spectroscopy was carried out to investigate binding between Pt2 L and hTel GQ. Measurements indicated that two molecules of Pt2 L bind with one molecule of hTel GQ. The inter‐spin distance measured between the two bound Pt2 L, together with molecular docking analyses, revealed that Pt2 L predominately binds to the neighboring narrow and wide grooves of the G‐tetrads as hTel adopts the antiparallel conformation. The design and synthesis of nitroxide tagged GQ binders, and the use of spin‐labeling/EPR to investigate their interactions with GQs, will aid the development of small molecules for manipulating GQs involved in crucial biological processes. Abstract : The groove armada : A dinuclear platinum(II) complex containing a nitroxide moiety (see structure) was synthesized and shown to specifically bind G‐quadruplex DNA and inhibit telomerase activity. EPR and molecular docking analyses revealed that the complex binds to neighboring grooves in an antiparallel G‐quadruplex. The work demonstrated a new strategy for developing small molecules for manipulating G‐quadruplexes involved in crucial biological processes.